The impact of climate on tourist destination choice - Richard S. J. Tol; Sharon Walsh (The Economic and Social Research Institute (ESRI), 2012)
We examine the determinants of holiday destination choice for tourists from 182 countries over a fifteen year time period. Our sample is much larger than that used by previous studies. The results are similar. Tourists prefer to stay relatively close to their home country. They like countries that have a long coast and lots of heritage. Tourists dislike poverty, and tourists from richer countries have a greater aversion to poverty. Tourists prefer politically unstable countries (all else being equal). Tourists like countries with high precipitation. Tourists like it hot, but not too hot. Tourists from warmer origins have stronger climate preferences.
Keywords: 330; climate; tourism; destination choice